Determination of latent hardening response for FeNiCoCrMn for twin-twin interactions. (1st April 2018) - Alkan, S.; Ojha, A.; Sehitoglu, H.
Abstract: Twin migration stresses and the associated latent hardening response in high entropy fcc alloys are derived corresponding to the dual interactions between all plausible twin systems. Employing an atomistically-informed, anisotropic analysis; the hardening matrix coefficients are calculated for the promising equiatomic FeNiCoCrMn high entropy alloy. The results point that the self-hardening coefficients (diagonal matrix components) are greater in magnitude than the latent hardening coefficients (off-diagonal components). This finding is a deviation from previous views in the literature which incorrectly attributed most of the hardening to latent terms. The predicted migration stresses and the strain hardening behavior exhibit a strong deviation from the Schmid law. The theoretical predictions are demonstrated to be in well agreement with the experimental trends. Furthermore, the local deviations from the stoichiometric chemical composition are shown to be of cardinal importance in the atomistic scale fault energy barrier levels. Graphical abstract: Image 1